Model Penataan Ruang Belajar di Rumah sesuai Gaya Belajar Anak pada Masa New Normal - Lindarto, Dwi; Rahman, Masyithah; Haq, Khadijah Zahira (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 9 No 1 (2022): April 2022, 2022)
A shift from school-based to online learning at home has caused problems during the covid-19 pandemic. The unpreparedness of homes to accommodate school activities, as well as parents’ limited capacity to act as teachers at home, are among major obstacles to online-home-learning-related practices. This study aims to examine the arrangement of the study space in accordance with the child's learning style. The outcome is to make homes comfortable places to study for families and their children. Taking SDIT Zahira Medan as its case study, this study uses behavioral analysis and qualitative-descriptive approaches to identifying associated problems and presenting them using a place-centered mapping principle. Using Miles and Huberman model and a cross-tabulation of both learning styles and properties of study rooms results in an optimum spatial arrangement and learning media that need to be considered in accordance with attributes proposed by Weisman. The results of the analysis show that visual, auditory, and kinesthetic learning styles require specific types and arrangements of study tables and chairs, the character of tools to support learning activities, and indoor and outdoor spaces dedicated to learning. This research is useful for improving children's learning achievement in terms of the pedagogical setting of 'study at home' activities in the new normal era of the covid-19 pandemic. Keywords : behavioral architecture, new normal era, learning style, paedagogic setting   Abstrak Pergeseran dari pendidikan berbasis sekolah ke pendidikan berbasis online di rumah menimbulkan masalah tersendiri di masa pandemi Covid-19. Ketidaksiapan rumah dalam mengakomodasi kegiatan sekolah dan keterbatasan para orang tua dalam mengambil peran para guru adalah bagian dari kendala utama dalam praktek ‘belajar online di rumah.’ Tujuan penelitian ini adalah mengkaji penataan ruang belajar yang sesuai dengan gaya belajar anak untuk menjadikan rumah sebagai tempat belajar yang nyaman bagi anak dan keluarga. Dengan pendekatan arsitektur perilaku dan menggunakan metode kualitatif deskriptif, dilakukan pemetaan masalah secara place-centered mapping dengan studi kasus sekolah SDIT Zahira Medan. Dengan analisis model Miles dan Huberman dan tabulasi silang atas gaya belajar dan properties ruang belajar diperoleh optimasi tatanan ruang dan media belajar yang perlu mendapat perhatian sesuai atribut Weisman. Hasil analisis menunjukkan bahwa gaya belajar visual, auditori dan kinsestetik memerlukan jenis dan tatanan meja kursi belajar, karakter alat  pendukung belajar, tempat belajar di dalam ruangan ( indoor ) dan di luar ruangan ( outdoor ) secara spesifik. Penelitian ini bermanfaat bagi peningkatan prestasi belajar anak dari sisi setting paedagogis kegiatan ‘belajar di rumah’ pada era new normal pandemic covid-19. Kata kunci: arsitektur perilaku, era new normal , gaya belajar, setting paedagogi